Quality of Life Domains in Breast Cancer Survivors: The Relationship Between Importance and Satisfaction Ratings - Hinz, Andreas; Zenger, Markus; Schmalbach, Bjarne; Brähler, Elmar; Hofmeister, Dirk; Petrowski, Katja (Frontiers in Psychology, 2022)
Objectives: Quality of life (QoL) has been the focus of increasing interest in oncology. QoL assessment instruments implicitly assume that each QoL domain has the same meaning for each patient. The objective of this study was to analyze the importance of and the satisfaction with QoL domains and to analyze the relationship between the two. Methods: A sample of 308 breast cancer survivors was examined twice with a three-month time interval. The women completed the two QoL questionnaires Questions of Life Satisfaction (FLZ-M), which measures participants’ satisfaction with eight QoL domains and the subjective importance of those domains to them, and the EORTC QLQ-C30. A sample of 1,143 women from the general population served as controls. Results: Compared with the general population sample, the patients were less satisfied with their health and more satisfied with all other QoL domains. The subjective importance of health was lower in the patients’ sample (Effect size: d = 0.38). Satisfaction with health and importance of health were slightly positively correlated (r between 0.05 and 0.08). The effect of QoL domain importance on general QoL was small (beta between -0.05 and 0.11), and interaction effects between domain importance and satisfaction on the prediction of global QoL were negligible. Conclusion: In addition to satisfaction with QoL dimensions, the subjective importance of these dimensions is relevant for psychooncological research and treatment. Health is not the only relevant QoL domain in breast cancer survivors, other domains such as finances also deserve health care providers’ attention.